Water level response measurement in a steel cylindrical liquid storage tank using image filter processing under seismic excitation. (15th February 2018) - Kim, Sung-Wan; Choi, Hyoung-Suk; Park, Dong-Uk; Baek, Eun-Rim; Kim, Jae-Min
Highlights: The method of measuring the water level in a liquid storage tank using images is suggested. The commercial digital camcorder is used as a sensor for measuring the water level response. The image filter processing is used for the reduction of the noise of the fluid induced by the reflection of light. The reliability of the water level response is found to be reliable. Abstract: Sloshing refers to the movement of fluid that occurs when the kinetic energy of various storage tanks containing fluid (e.g., excitation and vibration) is continuously applied to the fluid inside the tanks. As the movement induced by an external force gets closer to the resonance frequency of the fluid, the effect of sloshing increases, and this can lead to a serious problem with the structural stability of the system. Thus, it is important to accurately understand the physics of sloshing, and to effectively suppress and reduce the sloshing. Also, a method for the economical measurement of the water level response of a liquid storage tank is needed for the exact analysis of sloshing. In this study, a method using images was employed among the methods for measuring the water level response of a liquid storage tank, and the water level response was measured using an image filter processing algorithm for the reduction of the noise of the fluid induced by light, and for the sharpening of the structure installed at the liquid storage tank. A shaking table test was performed to verify the validity of the method of measuring the water level response of a liquid storage tank using images, and the result was analyzed and compared with the response measured using a water level gauge.